Surface chemistry of nanobiomaterials : applications of nanobiomaterials - Grumezescu, Alexandru Mihai (Elsevier Science, 2016)
Surface Chemistry of Nanobiomaterials brings together the most recent findings regarding the surface modification of currently used nanomaterials, which is a field that has become increasingly important during the last decade. This book enables the results of current research to reach those who wish to use this knowledge in an applied setting. Leading researchers from around the world present various types of nanobiomaterials, such as quantum dots (QDs), carbon nanotubes, silver nanoparticles, copper oxide, zinc oxide, magnesium oxide, magnetite, hydroxyapatite and graphene, and discuss their related functionalization strategies. This book will be of interest to postdoctoral researchers, professors and students engaged in the fields of materials science, biotechnology and applied chemistry. It will also be highly valuable to those working in industry, including pharmaceutics and biotechnology companies, medical researchers, biomedical engineers and advanced clinicians.